The exploitation argument against commercial surrogacy - Wilkinson, Stephen (Bioethics, 2003)
This paper discusses the exploitation argument against commercial surrogacy: the claim that commercial surrogacy is morally objectionable because it is exploitative. The following questions are addressed. First, what exactly does the exploitation argument amount to? Second, is commercial surrogacy in fact exploitative? Third, if it were exploitative, would this provide a sufficient reason to prohibit (or otherwise legislatively discourage) it? The focus throughout is on the exploitation of paid surrogates, although it is noted that other parties (e.g. ‘commissioning parents’) may also be the victims of exploitation. It is argued that there are good reasons for believing that commercial surrogacy is often exploitative. However, even if we accept this, the exploitation argument for prohibiting (or otherwise legislatively discouraging) commercial surrogacy remains quite weak. One reason for this is that prohibition may well ‘backfire’ and lead to potential surrogates having to do other things that are more exploitative and/or more harmful than paid surrogacy. It is concluded therefore that those who oppose exploitation should (rather than attempting to stop particular practices like commercial surrogacy) concentrate on: (a) improving the conditions under which paid surrogates ‘work’; and (b) changing the background conditions (in particular, the unequal distribution of power and wealth) which generate exploitative relationships.